2012
DOI: 10.1039/c2cc35643k
|View full text |Cite
|
Sign up to set email alerts
|

Cathode photoelectrochemical sensing of copper(ii) based on analyte-induced formation of exciton trapping

Abstract: The analyte-induced formation of exciton trapping leads to the decrease of cathode photocurrent of mercapto-capped CdTe quantum dots (QDs), which produces a sensitive cathode photoelectrochemical method for selective sensing of trace Cu(2+) as the analyte with a linear range from 0.06 to 100 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 24 publications
2
57
0
Order By: Relevance
“…[53] The influence of Cu 2 + on the photocurrent at aG L-MoS 2 /C 3 N 4 /ITO electrode was found to be concentration-dependent, as is evident from Figure 10 A. This phenomenon is at variancew ith some literature reports, [54,55] which indicated that as the concentration of Cu 2 + was increased, the photocurrentgradually decreased. It was speculated that Cu 2 + captured electrons from the surface of the platinum wire and was reduced to Cu.…”
Section: Electrochemical Propertiesmentioning
confidence: 65%
See 1 more Smart Citation
“…[53] The influence of Cu 2 + on the photocurrent at aG L-MoS 2 /C 3 N 4 /ITO electrode was found to be concentration-dependent, as is evident from Figure 10 A. This phenomenon is at variancew ith some literature reports, [54,55] which indicated that as the concentration of Cu 2 + was increased, the photocurrentgradually decreased. It was speculated that Cu 2 + captured electrons from the surface of the platinum wire and was reduced to Cu.…”
Section: Electrochemical Propertiesmentioning
confidence: 65%
“…When GL-MoS 2 / C 3 N 4 was irradiated with visible light,t he materiala bsorbed photonst og enerate excited electron and hole pairs. The generated holes could migrate to the surface of GL-C 3 N 4 ,a nd then transfer to GL-MoS 2 due to its suitable band-edge positions and good lattice matching with GL-C 3 N 4 , [33,54] which could enhance light harvesting and promote photogenerated charge separation. The photogenerated electrons could be easily transferred to the ITO electrode and generate ap hotocurrent because of the low energy level of the conduction band of ITO, [26,55] promoting the effective separation of electron-hole pairs.…”
Section: Electrochemical Propertiesmentioning
confidence: 98%
“…Based on the quantum photoelectric effect of quantum dots (QDs), a "signal on" visual method has been proposed for immunoassay of protein via the formation of insoluble reduction product of nitro blue tetrazolium by the photoelectron escaped from the QDs labeled to the secondary antibody under light excitation [25], and a "signal off" PEC method has also been reported for selective sensing of trace Cu 2+ by the analyte-induced formation of exciton trapping [26]. This work further combined the "signal off" PEC method with sandwich-type immunosensing strategy to develop a simple and sensitive PEC immunoassay method by using CuO NPs to label the secondary antibody.…”
Section: Introductionmentioning
confidence: 99%
“…This work further combined the "signal off" PEC method with sandwich-type immunosensing strategy to develop a simple and sensitive PEC immunoassay method by using CuO NPs to label the secondary antibody. As shown in Scheme 1, the CdS QDs was coated on the surface of F-doped tin oxide (FTO) electrode to form CdS QDs/ FTO electrode, which could produce the photocurrent by the photo induced exciton process [26]. Meanwhile, the CuO NPs were dissolved with acid after immunocomplex was formed, and the obtaining Cu 2+ solution was dropped on the CdS QDs/FTO electrode to induce the exciton trapping sites, which blocked the escape of photoelectron and thus quenched the photocurrent of QDs.…”
Section: Introductionmentioning
confidence: 99%
“…Many PEC sensors have been fabricated to detect cells [4,5], proteins [6,7], DNA [8][9][10], pesticides [11], small molecules [12][13][14][15], and metal ions [16][17][18]. Encouraged by the application in DNA detection, we think that the PEC technique for microRNA detection is feasible.…”
Section: Introductionmentioning
confidence: 99%